2013
DOI: 10.1063/1.4802257
|View full text |Cite
|
Sign up to set email alerts
|

Note: Generation of Raman laser beams based on a sideband injection-locking technique using a fiber electro-optical modulator

Abstract: Two phase-coherent Raman laser beams with a frequency offset of 6.835 GHz were generated by sideband injection-locking technique. A master diode laser was phase-modulated at 6.835 GHz by a fiber electro-optic modulator. A slave diode was injection-locked to the -1 sideband of the phase-modulated beam, and another diode was locked to the master laser carrier. This method produced stable and spatially separated Raman lasers with a large frequency shift range (>180 MHz). The relative linewidth of these two beams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The phase noise relationship between the Raman lasers and the gravimeter as shown as follow: There are many methods to obtain Raman lasers. For example, light double or multiple passes a high frequency AOM [18] or is sideband modulated by an EOM with a modulating frequency of 3.4 GHz (filtering out the ±1 order as the Raman lasers) [19] or two lights are offset frequency locked with a frequency difference of 6.834 GHz [4,20]. In our design, we choose the phase locking technique to realize Raman lasers.…”
Section: Blow Away F=2 Laser and Detection Lasermentioning
confidence: 99%
“…The phase noise relationship between the Raman lasers and the gravimeter as shown as follow: There are many methods to obtain Raman lasers. For example, light double or multiple passes a high frequency AOM [18] or is sideband modulated by an EOM with a modulating frequency of 3.4 GHz (filtering out the ±1 order as the Raman lasers) [19] or two lights are offset frequency locked with a frequency difference of 6.834 GHz [4,20]. In our design, we choose the phase locking technique to realize Raman lasers.…”
Section: Blow Away F=2 Laser and Detection Lasermentioning
confidence: 99%
“…[10] In these optical systems, the fluctuation of power ratio between two-frequency components after a TA has a significant influence on the preparation efficiency of cold atoms or the phase of a Raman-type atom interferometer induced by the differential Raman light shift, which may deteriorate the ultimate level of performance in terms of accuracy as an inertial sensor. [15][16][17][18][19][20][21][22][23][24][25] Early studies on semiconductor laser amplifiers showed that gain-saturation-induced nonlinearity could lead to a shape distortion and spectral broadening of optical pulses as a result of the self-phase modulation. Agrawal et al obtained simplified equations governing the dynamics of the amplifica-tion process in the approximation that the optical pulse width was much larger than the intraband relaxation time.…”
Section: Introductionmentioning
confidence: 99%